2016
DOI: 10.1016/j.jcis.2015.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced perfume surface delivery to interfaces using surfactant surface multilayer structures

Abstract: Enhanced surface delivery and retention of perfumes at interfaces are the keys to their more effective and efficient deployment in a wide range of home and personal care related formulations. It has been previously demonstrated that the addition of multivalent counterions, notably Ca(2+), induces multilayer adsorption at the air-water interface for the anionic surfactant, sodium dodecyl-6-benzenesulfonate, LAS-6. Neutron reflectivity, NR, measurements are reported here which demonstrate that such surfactant su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, as is the case with MD simulations, very little research has been reported on the interactions of small molecules and surfactant monolayers. The experimental investigations that have been reported were focussed on oil 44,45 and fragrance 46,47 molecules. Only recently have we reported an interdisciplinary investigation of a drug molecule with a SDS monolayer 48 .…”
Section: Introductionmentioning
confidence: 99%
“…However, as is the case with MD simulations, very little research has been reported on the interactions of small molecules and surfactant monolayers. The experimental investigations that have been reported were focussed on oil 44,45 and fragrance 46,47 molecules. Only recently have we reported an interdisciplinary investigation of a drug molecule with a SDS monolayer 48 .…”
Section: Introductionmentioning
confidence: 99%
“…A loss of volatile compounds, declines their commercial value . Therefore, special aqueous based solubilization and delivery systems have been proposed for fragrant molecules to thwart their chemical instability, enhance their water solubility, and decrease their volatility for persistent fragrance over longer times. Surfactant aided microencapsulation is becoming increasingly important owing to good capability for solubilization, stabilization, and controlled transport of volatile fragrant molecules. Recently, neutron reflectivity was utilized by Bradbury et al , and Penfold et al , to explore the coadsorption at the air–solution interface of some perfume molecules for optimizing their performance in different formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Finally the results further illustrate the rich opportunities for the manipulation of the surface properties in such systems, in the applications related to adjusting wetting behaviour and efficient enhanced interfacial delivery (3)(4)(5), and in enhancing emulsification and solubilisation properties (28). The potential applications at the air-…”
Section: Discussionmentioning
confidence: 88%
“…It provides the opportunity to manipulate wetting properties in many diverse applications. The surface multilayer structures also provide an efficient near surface reservoir for rapid, enhanced and prolonged delivery of other active agents in formulations, for example, in perfume delivery (4,5). Furthermore it offers greater opportunities for improved solubilisation properties and more effective emulsification.…”
Section: Introductionmentioning
confidence: 99%